Stevens–Johnson syndrome and toxic epidermal necrolysis associated with increased risk of developing psychiatric disorders: A retrospective population‐based cohort study in Taiwan. Issue 10 (10th June 2022) - Chiang, Chien‐Ping; Hung, Chih‐Tsung; Chen, Yi‐Hsien; Chen, Chih‐Yu; Soong, Chen‐Yeu; Liu, Sheng‐Wen; Liu, Hsi‐Ling; Ma, Jun; Chung, Chi‐Hsiang; Tsao, Chang‐Huei; Sun, Chien‐An; Chien, Wu‐Chien; et al.
Abstract: Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are life‐threatening adverse reactions to drugs and psychological sequelae are also observed to follow the trauma of widespread epidermal necrolysis. To delineate the association between SJS and TEN, and psychiatric disorders, we conducted a retrospective population‐based cohort study by including 212 patients diagnosed with first‐time SJS or TEN in Taiwan between 2000 and 2013 and 669 population controls. Adjusted hazard ratios were calculated after adjusting for sex, age, comorbidity in the form of Charlson comorbidity index, and facility level of care. Overall, SJS or TEN was associated with an increased risk of developing psychiatric disorders including schizophrenia, major depressive disorder, mania, anxiety, and bipolar with an adjusted hazard ratio of 1.392 (95% CI, 1.192–1.625; p < 0.001). Particularly, the adjusted hazard ratios of psychiatric disorders were 1.290 (95% CI, 1.105–1.506; p < 0.001) for SJS and 1.855 (95% CI, 1.587–2.167; p < 0.001) for TEN.